2023
DOI: 10.1002/adfm.202306060
|View full text |Cite
|
Sign up to set email alerts
|

High Ionic Conductivity Motivated by Multiple Ion‐Transport Channels in 2D MOF‐Based Lithium Solid State Battery

Abstract: Metal‐organic frameworks (MOFs) have been proposed as novel fillers for constructing polymer solid electrolytes based composite electrolytes. However, MOFs are generally used as passive fillers, in‐depth revealing the binding mode between MOFs and polyethylene oxide (PEO), the critical role of MOFs in facilitating Li+ transport in solid electrolytes is full of challenges. Herein, inspired by density functional theory (DFT) the 2D‐MOF with rich unsaturated metal coordination sites that can bind the O atom in PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…16,22,28 It should be noted that MOF materials were usually vacuum heat-treated to expose open metal sites before use. 33,38,44 SEM images (Figure S2) reveal that the morphologies of 15%Cu-MOF/P−Li and 15%Ni-MOF/P−Li are flat and smooth, similar to P−Li, and Cu/Ni elements are uniformly distributed on the surface of SCEs, confirming the uniform dispersion of MOF-74 particles in the PEO matrix. 37 We found that excessive Cu-MOF-74 causes particle aggregation, which degrades the Li-ion transport efficiency.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…16,22,28 It should be noted that MOF materials were usually vacuum heat-treated to expose open metal sites before use. 33,38,44 SEM images (Figure S2) reveal that the morphologies of 15%Cu-MOF/P−Li and 15%Ni-MOF/P−Li are flat and smooth, similar to P−Li, and Cu/Ni elements are uniformly distributed on the surface of SCEs, confirming the uniform dispersion of MOF-74 particles in the PEO matrix. 37 We found that excessive Cu-MOF-74 causes particle aggregation, which degrades the Li-ion transport efficiency.…”
Section: Resultsmentioning
confidence: 84%
“…Solution casting was used to prepare the PEO-based SCEs as shown in Figure a. ,, It should be noted that MOF materials were usually vacuum heat-treated to expose open metal sites before use. ,, SEM images (Figure S2) reveal that the morphologies of 15%Cu-MOF/P–Li and 15%Ni-MOF/P–Li are flat and smooth, similar to P–Li, and Cu/Ni elements are uniformly distributed on the surface of SCEs, confirming the uniform dispersion of MOF-74 particles in the PEO matrix …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Metal−organic frameworks (MOFs), a new type of periodic porous crystal material, possessing large specific surface area, high porosity, and controllable chemical compositions and structures, have potential applications in many fields such as ion conduction, 14,15 energy storage, 16 and EMW absorption. 17−20 However, the electrical insulation of most MOFs hinders their application in EMW absorption materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), a new type of periodic porous crystal material, possessing large specific surface area, high porosity, and controllable chemical compositions and structures, have potential applications in many fields such as ion conduction, , energy storage, and EMW absorption. However, the electrical insulation of most MOFs hinders their application in EMW absorption materials. To improve the EMW absorption ability of MOF-based materials, high-temperature calcination in an inert atmosphere is usually adopted to convert the MOF template into a porous carbon-based material containing metal/metallic compounds .…”
Section: Introductionmentioning
confidence: 99%